Specialized bark-gnawing beetles reveal phragmotic defence and subcortical ecology in the Cretaceous - Li, Yan-Da; Leschen, Richard A B; Kolibáč, Jiří; Engel, Michael S; Zhang, Zhi-Qiang; Yu, Yali; Huang, Diying; Cai, Chenyang (Proceedings. Biological sciences, 2025)
Ecological interactions are fundamental to understanding species' trophic relationships and the evolution of ecosystem functions. However, the fossil record seldom captures these intricate dynamics, as most fossils preserve individual organisms rather than the interactions that shaped ancient ecosystems. Here, we describe a new genus of bark-gnawing beetles (Trogossitidae), Rutrizoma gen. nov., from mid-Cretaceous amber in northern Myanmar. This fossil genus reveals a rare combination of predatory and antipredatory adaptations, shedding light on the ecological complexity of Mesozoic forest ecosystems. Rutrizoma has specialized morphological features, such as shortened elytra and unidentate mandibles, suggesting an active predatory lifestyle in narrow wood galleries. Interestingly, some morphological traits of Rutrizoma mirror those of its potential prey, particularly bostrichid beetles, from the same amber deposit. One such trait is its specialized abdominal declivity, which probably functioned as a protective shield against predators and competitors, representing marked convergence with the elytral declivity of other subcortical beetles, such as bark and ambrosia beetles (Scolytinae and Platypodinae) and Bostrichidae. The presence of phoretic mites associated with Rutrizoma, along with co-preserved bostrichid prey, underscores the complex community dynamics beneath Cretaceous tree bark. This finding reveals a subcortical ecosystem that parallels modern ecological interactions.
Keywords: predátorské chování; brouci; Cretaceous; zkameněliny; ecological interaction; Ecosystem; beetle; Myanmar; defence; Fossils; biologická evoluce; jantar; phragmosis; Predatory Behavior; Animals; Biological Evolution; zvířata; Coleoptera; Amber; ekosystém